Unmasking the Healthcare Issues Slipping through the Cracks during the Pandemic - Manas Pustake; Ciara Egan; Annora A. Kumar (University Library System, University of Pittsburgh, 2021)
Over the last nine years, the International Journal of Medical Students (IJMS) has been assisting medical students to seek excellence in research. From its conception, IJMS has been publishing tri-annually; however, due to the huge number of article submissions to the journal, IJMS is now publishing four issues every year. Since the start of the COVID-19 pandemic, there has been a rise in the incidence of crime and interpersonal violence, including sexual assault. Despite this, it has also been found that the number of such offences reported has decreased. In this editorial, we bring to light the under-recognized issue of sexual assault by highlighting an article regarding medical students' training in caring for assault victims that will be published in this issue. We also discuss other under-recognized healthcare problems in this editorial. This upcoming issue of IJMS is one that not only contains research and experience pieces about the COVID-19 pandemic's ramifications; beautifully recounted and inspiring experiences from medical students can also be found in this issue. Combined with the intriguing case reports and a letter-to-the-editor, we are sure that this upcoming issue will pique the curiosity of our worldwide readership.